Study on the mechanism and clinical value of miR-210-3p and miR-582-5p in acute myocardial infarction by targeting MXD1 - Shanshan Liu; Jing Han; Shufang Gao (Journal of Cardiothoracic Surgery)
Abstract Background Acute myocardial infarction (AMI) occurs rapidly and is a major cause of death in patients with coronary artery disease (CAD). To explore new biomarkers of AMI and its pathogenesis. Methods Mining key miRNAs (miR-210-3p, miR-582-5p) and gene (MXD1) using the GEO and starbase databases. The expression of miRNAs and related genes was detected by qPCR. The clinical value of miR-210-3p/miR-582-5p was evaluated by constructing ROC curves. The targeted regulation of MXD1 by miR-210-3p and miR-582-5p was demonstrated by the dual-luciferase assay and transfection of mimics. The levels of cTnI, MDA, and Fe2+ were measured using kits. Overexpressing miR-210-3p, miR-582-5p, and MXD1 to explore their roles in hypoxia-induced cardiomyocyte injury. Results MiR-210-3p and miR-582-5p were deficient in AMI patients and hypoxic cardiomyocytes, while MXD1 was high-expressed. MiR-210-3p combined with miR-582-5p could well distinguish ST elevation-AMI and non-ST elevation-AMI patients from CAD patients, with AUC of 0.865 (0.806–0.923) and 0.813 (0.744–0.881), respectively. The mimics of miR-210-3p and miR-582-5p significantly reduced luciferase activity in cells transfected with the wild-type luciferase vector of MXD1 and inhibited MXD1 expression, which was promoted by their inhibitors. Overexpression of miR-210-3p/miR-582-5p saved hypoxia-induced ferroptosis, which was reversed by co-transfection of the MXD1 plasmid. Conclusion MiR-210-3p and miR-582-5p are good classifiers for AMI patients and CAD patients. They can negatively regulate the expression of MXD1 by directly targeting its mRNA, inhibiting ferroptosis of hypoxic cardiomyocytes, and may be effective predictors of CAD progression to AMI.